Drinking Water Quality in the Circumpolar North: An Examination of Waterborne Giardia and Cryptosporidium in Iqaluit and Rigolet, Canada - Masina, Stephanie (University of Guelph, 2018)
Drinking water challenges often exist in the Circumpolar North; therefore, this research examined northern drinking water quality using three studies. First, a scoping review summarized circumpolar drinking water quality and human health literature, identifying few studies examining waterborne parasites. Second, Giardia and Cryptosporidium were examined in surface water from Iqaluit, Nunavut. Using EcoHealth approaches, water samples (n=55) were collected and tested for these parasites. 20.0% and 1.8% of samples tested positive for Giardia and Cryptosporidium, respectively. The odds of detecting parasites were greater with lower air and water temperatures compared to higher temperatures. Third, we explored waterborne Giardia and Cryptosporidium in Rigolet, Labrador. Of the drinking water sources tested (n=4), Giardia and Cryptosporidium were detected in tap water and the municipal water reservoir. This community-based research contributes to the growing literature on northern drinking water quality, and was intended to inform locally-specific and relevant water quality management in northern communities. ArcticNet Queen Elizabeth II Graduate Scholarship in Science and Technology University of Guelph University of Guelph